Legacy Teachers™: Celebrating Our Patients as Teachers - Elizabeth Garrett; Carrie Nicholson; Linda Headrick (Association of American Medical Colleges, 2015)
Abstract Introduction At the University of Missouri-Columbia School of Medicine, providing effective patient-centered care is core to our mission. We believe this requires the values of generosity, self-reflection, humility, gratitude, and treating the patient as a complete person. We expect our students to share these values. The Legacy Teachers program was designed and implemented to encourage students to focus on the physician-patient relationship, to reflect on a particular patient who taught them lessons they would carry with them through their professional careers, to honor and thank our patients as teachers, to highlight for patients and their families the positive aspects of having medical students involved in their care, and to help with transitions in the students' emerging professional roles. Methods Legacy Teachers is a voluntary program where third-year students are invited to participate by writing a two− to three-page essay or a poem or creating artwork about a patient they cared for during their third year. Poems and artwork are accompanied by a one-page summary describing what their Legacy Teacher taught them. The Legacy Teachers are invited to a celebratory luncheon that occurs every spring. On the first day of the third year of medical school, each clerkship director encourages students to participate in Legacy Teachers by including a brief discussion of the program in clerkship orientation. Results Legacy Teachers started with a focus on the third-year medical school class. In the early years, the number of students participating was small. Since we began including the second-year students at the luncheon, third-year submission rates have significantly increased. Thirty to forty percent of each third-year class now participates. The growing participation in this voluntary experience is evidence of strong student endorsement of the program. The number of participating faculty has also grown over the years, steadily rising from approximately 10 in the first year to 30 at the most recent luncheon. A wide variety of Legacy Teachers are recognized each year. They come from both rural and urban areas covering 49% of Missouri counties. Discussion The overall objective of Legacy Teachers is to contribute to an institutional climate that promotes patient-centered care. At the outset, we also believed this program could offer a great deal to the Legacy Teachers and their families. They repeatedly tell us that they had no idea that they could have taught a young physician something that made a difference in their professional lives.